Molecular Characterization, Expression and In Situ Hybridization Analysis of a Pedal Peptide/Orcokinin-type Neuropeptide in Cuttlefish Sepiella japonica - Li, Gong; Qiu, Jiayin; Cao, Huimin; Zheng, Libing; Chi, Changfeng; Li, Shuang; Zhou, Xu (Current Protein and Peptide Science, 2024)
Background: Neuropeptide pedal peptide (PP) and orcokinin (OK), which are structurally related active peptides, have been widely discovered in invertebrates and constitute the PP/OK neuropeptide family. They have complex structures and play myriad roles in physiological processes. To date, there have been no related reports of PP/OK-type neuropeptide in cephalopods, which possess a highly differentiated multi-lobular brain. Methods: Rapid Amplification of cDNA Ends (RACE) was employed to obtain the open reading frame (ORF) of PP/OK-type neuropeptide in Sepiella japonica (termed as Sj-PP/OK). Various software were used for sequence analysis. Semi-quantitative PCR was applied to analyze the tissue distribution profile, quantitative real-time PCR (qRT-PCR) was used to study spatio-temporal expression throughout the entire growth and development period, and in situ hybridization (ISH) was employed to observe the tissue location of Sj-PP/OK. Results: in the present study, we identified the ORF of Sj-PP/OK. The putative precursor of Sj-PP/ OK encodes 22 mature peptides, of which only tridecapeptides could undergo post-translationally amidated at C-terminus. Each of these tridecapeptides possesses the most conserved and frequent N-terminus Asp-Ser-Ile (DSI). Sequence analysis revealed that Sj-PP/OK shared comparatively low identity with other invertebrates PP or OK. The tissue distribution profile showed differences in the expression level of Sj-PP/OK between male and female. qRT-PCR data demonstrated that Sj-PP/OK was widely distributed in various tissues, with its expression level increasing continuously in the brain, optic lobe, liver, and nidamental gland throughout the entire growth and development stages until gonad maturation. ISH detected that Sj-PP/OK positive signals existed in almost all regions of the optic lobe except the plexiform zone, the outer edge of all functional lobes in the brain, epithelial cells and the outer membrane layer of the accessory nidamental gland. These findings suggest that Sj-PP/OK might play a role in the regulation of reproduction, such as vitellogenin synthesis, restoration, and ova encapsulation. Conclusion: The study indicated that Sj-PP/OK may be involved in the neuroendocrine regulation in cephalopods, providing primary theoretical basis for further studies of its regulation role in reproduction.
Keywords: Sepiella japonica